Segurança de Antidiabéticos Orais: Análise de Desproporcionalidade no Sistema Português de Farmacovigilância - Mendes, Diogo (2019)
Introduction: Our objective was to investigate associations between oral antidiabetics and adverse drug reactions through disproportionality analysis in the Portuguese Pharmacovigilance System database. Methods: Spontaneous reports of adverse drug reactions reported for oral antidiabetics (2008–2017) were considered. Adverse drug reactions were coded according to MedDRA (preferred term), and oral antidiabetics according to Anatomical Therapeutic Chemical classification (4th level). Associations between oral antidiabetics and adverse drug reactions were assessed through a case/non-case methodology, using reporting odds ratio (ROR) with 95% confidence interval (CI) to identify signals of disproportionate reporting. Results: A total of 413 cases (262 serious; 63.4%) containing 1047 adverse drug reactions were included. Signals of disproportionate reporting were found: i) alpha-glucosidase inhibitors – abdominal pain (ROR: 9.7 [2.5-37.7]) and flatulence (ROR: 76.1[13.0-444.4]); ii) Dipeptidyl peptidase-4 inhibitors – upper abdominal pain (ROR: 5.5[1.5-20.7]), headache (ROR: 5.5[1.5-20.7]) and acute pancreatitis (ROR: 22.0[2.6-189.9]); iii) Glucagon-like peptide-1 agonists – vomiting (ROR: 3.4[1.4-8.4]; iv) metformin – abdominal pain (ROR: 3.6[1.1-11.6]), diarrhea (ROR: 5.6[2.4-13.2]) and lactic acidosis (ROR: 76.9[4.7-1269.0]); v) SGLT2 inhibitors – candida infection (ROR: 51.5[2.8-950.1], diabetic ketoacidosis(ROR: 84.8[4.8-1487.8]), pollakiuria (ROR: 15.2[1.6-147.1]), somnolence (ROR:30.4[1.5-610.3] and urinary tract infection (ROR: 15.2[1.6-147.1]); vi) sulfonylureas – hypoglycemia (ROR: 44.8[14.4-139.8]). Conclusion: The results are in line with previous knowledge on the safety profiles of the different classes of oral antidiabetics, reinforcing the need to monitoring closely certain adverse drug reactions in clinical practice depending on the therapy prescribed to diabetic patients.